PEMBUATAN KATALIS BERBASIS KARBON AKTIF DARI TEMPURUNG KELAPA (Cocos nucifera) DIIMPREGNASI KOH PADA REAKSI TRANSESTERIFIKASI SINTESIS BIODIESEL - Zamhari, Mustain; Junaidi, Robert; Rachmatika, Nisa; Oktarina, Ayu (Politeknik Negeri Sriwijaya, 2021)
The Research has been carried out on KOH catalyst/activated carbon as a heterogeneous base catalyst with the impregnation method to be applied in making biodiesel from used cooking oil. Activated carbon from coconut shell carbonized in a furnace at 500oC for 4 hours. After that, activated carbon was impregnated in a KOH solution with a concentration of 1 N, 2N, 3 N, 4 N, and 5 N for 18,21 and 24 hours. Catalyst is analyzed with AAS (Atomic Absorption Spectrophotometry) to see the content of potassium absorbed in the activated carbon. Analyzed SEM (Scanning Electron Microscopy) to see the characteristics of the catalyst that has been produced. Best condition which produced the catalyst with the highest potassium content after impregnation is 97.00% was obtained at a concentration of 5 N KOH with an impregnation time of 21 hours. Making biodiesel, variations of catalyst 1,3, and 5% are carried out with a reaction temperature of 45,55,65,75oC,cooking oil:methanol ratio of 1:6. The best biodiesel is obtained from a catalyst 3% at 55oC with a yield of 87.72%. Characteriszation of methyl ester product fulfill standart of biodiesel viscosity 4.7622 gr/ml, denistas 0.8709 gr/ml, acid number 1.4027 mgKOH/g, water content 0.0266%, flash point 176oC.